An overview of the potential strategies for NK cell‐based immunotherapy for acute myeloid leukemia. Issue 12 (18th August 2016) - Sinha, Chandrima; Cunningham, Lea C.
Abstract: Patients with acute myeloid leukemia (AML) have relatively low survival rates compared to patients with other pediatric cancers. Relapse is frequent with conventional treatment and is a major cause of morbidity and mortality. Natural killer (NK) cells offer an alternative approach to chemotherapy that combats relapse by substantially eradicating AML blasts. New methods for enhancing NK cell activation and expression of the activating ligand on target malignant cells will increase the likelihood of success with this approach. We review these latest discoveries in NK cell‐based therapy for AML and delineate recent advances in sensitizing AML cells to NK cell‐mediated immunosurveillance.